2022
DOI: 10.1002/jbt.23262
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of moderate ROS and PARP‐1 contributes to sustainable proliferation of conditionally reprogrammed keratinocytes

Abstract: Conditionally reprogrammed cell (CRC) technique is a promising model for biomedical and toxicological research. In the present study, our data first demonstrated an increased level of PARP-1 in conditionally reprogrammed human foreskin keratinocytes (CR-HFKs). We then found that PARP inhibitor ABT-888 (ABT), reactive oxygen species (ROS) scavenger N-acetyl-L-cysteine (NAC), or combination (ABT + NAC) were able to inhibit cell proliferation, ROS, PARP-1, and ROS related protein, NRF2, and NOX1. Interestingly, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has been reported that moderate ROS are important for cell growth and differentiation ( Liu et al, 2023 ). During chondrogenesis, ROS are required for cell growth and differentiation of BMSCs ( Lu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that moderate ROS are important for cell growth and differentiation ( Liu et al, 2023 ). During chondrogenesis, ROS are required for cell growth and differentiation of BMSCs ( Lu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… 37 This study found that Xn treatment activates AMPK and reduces NLRP3 inflammasome activation. At the same time, AMPK performs an anti-inflammatory function through the regulation of Nrf2, which is a crucial player in the cellular defense against oxidative 38 and xenobiotic or nutrient stress and can be a therapy target for chronic pain. 39 Nrf2 inducers exert potent analgesic effects in a variety of murine models of chronic pain.…”
Section: Discussionmentioning
confidence: 99%